Developmental amnesia and its relationship to degree of hippocampal atrophy. - Isaacs, E; Vargha-Khadem, F; Watkins, K; Lucas, A; Mishkin, M; Gadian, D (2003)
Two groups of adolescents, one born preterm and one with a diagnosis of developmental amnesia, were compared with age-matched normal controls on measures of hippocampal volume and memory function. Relative to control values, the preterm group values showed a mean bilateral reduction in hippocampal volume of 8-9% (ranging to 23%), whereas the developmental amnesic group values showed a reduction of 40% (ranging from 27% to 56%). Despite equivalent IQ and immediate memory scores in the two study groups, there were marked differences between them on a wide variety of verbal and visual delayed memory tasks. Consistent with their diagnosis, the developmental amnesic group was impaired relative to both other groups on nearly all delayed memory measures. The preterm group, by contrast, was significantly impaired relative to the controls on only a few memory measures, i.e., route following and prospective memory. We suggest that early hippocampal pathology leads to the disabling memory impairments associated with developmental amnesia when the volume of this structure is reduced below normal by approximately 20-30% on each side. Whether this is a sufficient condition for the disorder or whether abnormality in other brain regions is also necessary remains to be determined.